Detection of the technical-tactical pattern of the scoring actions in judo in the men`s category of -73 kg - Gutiérrez-Santiago, A.; Gentico-Merino, L. A.; Prieto-Lage, I. (International Journal of Performance Analysis in Sport, 2019)
The scoring actions determine the judoka winner in a combat. The scientific community has studied them, but these studies are especially descriptive. To this end, the purpose of this study is to discover and analyse the technical-tactical patterns of the scoring actions in judo combat. Ninety-one scoring actions were analysed (-73 kg males, Judo World Championship 2017) using different commonly used analysis techniques within the observational methodology: traditional statistical analysis, T-Patterns detection, sequential analysis delays and polar coordinates analysis. The tendency of scoring with leg and arm projections prevails (seoi-otoshi, ouchi-gari, tai-otoshi and uchi-mata). The more efficient technique on the ground was yoko-shiho-gatame. The waza-ari is three times more frequent than the ippon. The actions score mainly during the final stages of combat. The judokas with favourable scores score more points through immobilisations, with scores equal to leg techniques and with scores against sacrificial techniques. It is important to conduct the combat`s initiative because in most the actions, the judoka that scores has no penalties and the one who does not score does. A common pattern is achieving a waza-ari with a direct leg attack technique or a static arm technique.